Among Video Based Learning Web Based Learning and EFL Students Mastery of Conditional Sentences: A Study of Senior High School Level - Juniva J. Mangundap; Olga A. Rorintulus; Ceisy N. Wuntu (English Education Department, 2025)
This research explored the impact of Video Based Learning VBL and Web Based Learning WBL on enhancing the understanding of conditional sentences Types 1 2 and 3 among Grade 10 students at SMA UNKLAB Airmadidi Employing a quasi experimental design 60 students were assigned to two groups: one received instruction via VBL while the other was taught using WBL Pre test and post test results were examined using IBM SPSS Version 26 with both paired sample and independent sample t tests applied The paired sample t test indicated notable improvement in both groups The average score for the VBL group rose from 33 60 to 77 87 and for the WBL group from 33 20 to 59 73 The independent sample t test yielded a Sig 2 tailed value of 0 001 signifying a statistically significant difference between the groups While both approaches were effective VBL demonstrated a more substantial effect on students grammar proficiency Additionally analysis showed no significant difference in performance based on gender suggesting that both teaching methods were equally effective for male and female students Overall the findings underscore the advantages of incorporating digital media in grammar instruction with VBL particularly enhancing student engagement and understanding of complex grammar topics This study affirms the value of multimedia in English teaching and highlights the potential of visual and interactive content to boost learner motivation and success < p>